Sulfur Promotion in Au/C Catalyzed Acetylene Hydrochlorination. Issue 16 (25th February 2021) - Dawson, Simon R.; Pattisson, Samuel; Malta, Grazia; Dummer, Nicholas F.; Smith, Louise R.; Lazaridou, Anna; Allen, Christopher S.; Davies, Thomas E.; Freakley, Simon J.; Kondrat, Simon A.; Kiely, Christopher J.; Johnston, Peter; et al.
Abstract: The formation of highly active and stable acetylene hydrochlorination catalysts is of great industrial importance. The successful replacement of the highly toxic mercuric chloride catalyst with gold has led to a flurry of research in this area. One key aspect, which led to the commercialization of the gold catalyst is the use of thiosulphate as a stabilizing ligand. This study investigates the use of a range of sulfur containing compounds as promoters for production of highly active Au/C catalysts. Promotion is observed across a range of metal sulfates, non‐metal sulfates, and sulfuric acid treatments. This observed enhancement can be optimized by careful consideration of either pre‐ or post‐treatments, concentration of dopants used, and modification of washing steps. Pre‐treatment of the carbon support with sulfuric acid (0.76 m ) resulted in the most active Au/C in this series with an acetylene conversion of ≈ 70% at 200 ° C. Abstract : Sulfur has played a crucial role in providing stable and commercially viable gold catalysts for the production of VCM from acetylene hydrochlorination. This study explores a range of sulfur compounds and treatments, and demonstrates their versatility as promoters for the production of highly active catalysts.